The Sale of Multiple Assets with Private Information - He, Zhiguo (Review of Financial Studies, 2009)
[By generalizing the Leland and Pyle (1977) model to the case of multiple correlated assets, this paper studies the signaling and hedging behavior of an intermediary who sells multiple assets in financial markets. Based on information asymmetry, this paper demonstrates the intrinsic interdependence of risk management and asset selling for intermediaries, and obtains several testable empirical implications. For instance, an intermediary with a more diversified underlying portfolio will face greater liquidity (a smaller price impact) when selling assets to the market. Several applications are discussed, including bank loan sales and selling mechanisms.]